2009
DOI: 10.4102/ac.v9i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the outcome of information technology projects in South Africa: An empirical investigation

Abstract: Purpose:In developing countries such as South Africa, many organisations are reliant on information and communication technology (ICT) to provide accurate, relevant and timely information. For organisations to obtain and sustain a competitive advantage, ICT systems are constantly implemented, upgraded, modified or replaced. These initiatives are often managed as projects.While there is an increasing amount of both financial resources and effort being spent on ICT, these projects are not always delivered within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…And yet 46% are neutral about the constraints that NFR put on software projects. These are all common problems in ARE and consistent with reasons for project failure such as handling change, customer involvement, and requirements definition defined by Sonnekus and Labuschagne (2003) and Labuschagne et al (2009).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…And yet 46% are neutral about the constraints that NFR put on software projects. These are all common problems in ARE and consistent with reasons for project failure such as handling change, customer involvement, and requirements definition defined by Sonnekus and Labuschagne (2003) and Labuschagne et al (2009).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Six of these principles mostly define collaboration and interaction between customers and software practitioners; consequently, one can deduce from the results that the two parties are very collaborative. Good collaboration is essentially one of the reasons influencing project success in South Africa (Sonnekus & Labuschagne, 2003;Labuschagne et al, 2009). The fourth objective sought to get software practitioners receptivity vis-à-vis dynamic requirements.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of reasons why numerous studies [1][2][3] indicated that the IS project management is the immature discipline; it may because the performance of the projects still show its high failure rate [4]. As it was initiated by the Standish Group's report in the mid of 1990s, and the similar announcements were presented by numerous survey studies [5][6][7].…”
Section: Introductionmentioning
confidence: 88%